2018
DOI: 10.1093/eurpub/cky093
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of elder abuse in institutional settings: a systematic review and meta-analysis

Abstract: The prevalence of elder abuse in institutions is high. Global action to improve surveillance and monitoring of institutional elder abuse is vital to inform policy action to prevent elder abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
208
3
27

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 232 publications
(248 citation statements)
references
References 23 publications
10
208
3
27
Order By: Relevance
“…Little is known about elder abuse in nursing homes, and compared to research on other forms of interpersonal abuse, research about elder abuse in nursing homes is still in its infancy [1,2]. Although no national prevalence data are available in any country internationally, high rates of elder abuse and neglect have been reported in nursing homes, including Norway [1,3]. According to the World Health Organisation (WHO), elder abuse has been identified in almost every country where these institutions exist [4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Little is known about elder abuse in nursing homes, and compared to research on other forms of interpersonal abuse, research about elder abuse in nursing homes is still in its infancy [1,2]. Although no national prevalence data are available in any country internationally, high rates of elder abuse and neglect have been reported in nursing homes, including Norway [1,3]. According to the World Health Organisation (WHO), elder abuse has been identified in almost every country where these institutions exist [4].…”
Section: Introductionmentioning
confidence: 99%
“…The definition from 'Protecting Our Future: Report from the Working Group on Elder Abuse' (Ireland) includes physical, psychological, financial and sexual abuse, and neglect (Table 2) [12]. Abuse in nursing homes may also be categorized according to type of relation [1]; staff-toresident abuse [3,13], family-to-resident abuse [14,15] and resident-to-resident abuse, also called resident-toresident aggression [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may also include the violation of personal rights and neglect [1]. The WHO reported that around 1 in 6 people aged 60 years and older experience some form of abuse in their communities annually [7,8]. Furthermore, the prevalence of elder abuse has been reported to be 1-15%, and it may impact 1 in 10 elderly individuals each month [1].…”
Section: Introductionmentioning
confidence: 99%